Naplnění snu: Vybudování československé nemocnice v Bagdádu - Bartošová, Kateřina; Turková, Miloslava (Lidé města, 2005)
On March 15, 1925, Czech medical doctor - MUDr. Vlasta Kálalová made another significant step to fulfil her dream - to build a Czechoslovakian hospital in Baghdad. On that day, following many obstacles on the difficult journey from Constantinople further to the East she reached Baghdad, the Capital City of Iraq’s Kingdom - her future workplace. In this city she lived and worked, with a brief interruption in 1927, the next seven years. Shortly after arrival, she managed to acquire from the English colonial administration a license to practice medical profession. Since the start of her medical work, large number of patients came for help to the newly opened medical office, and so already in December 1925 a surgical clinic of MUDr. Vlasta Kálalová was established, based on approval secured from English authority - the so called “Mustausaf Czechoslovak”. She ran this “Czechoslovakian Dispensary for Surgical and Gynecology Maladies”, including a room for the sick and modern operating theatre, very successfully until 1932. She was assisted only by a Czech registered nurse and unqualified Assyrian assistant.